PENGARUH BRAND AMBASSADOR DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Mahasiswa Pengguna OPPO Smartphone Di Fakultas Ekonomi dan Bisnis Jurusan Manajemen Universitas Islam Malang) - Ahmad Rifa’i Maksum; Rois Arifin; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this study is to describe the brand ambassador, product quality, brand image and purchasing decisions and determine the influence and analyze the brand ambassador and product quality on purchasing decisions with brand image as an intervening variable. The method in this study is to use quantitative methods.The sample of this study were students of the Faculty of Economics and Business Management Department of Malang Islamic University by using purposive sampling, as many as 77 respondents. Methods in collecting data using questionnaires. The analytical method used in this study is the path analysis with SPSS 14.0 FOR WINDOWS.The result of this research indicate that brand ambassador have an insignificant effect on brand image, brand ambassador have no significant effect on purchasing decision, product quality has significant effect to brand image, product quality has significant effect on purchasing decision, brand image has significant effect to purchasing decision, and product quality direct influence on purchasing decisions is greater than the quality of products for purchasing decisions indirectly through brand image.Keywords: Brand Ambassador, Product Quality, Brand Image, and Purchase Decision.